Website Satisfaction dan commercial Friendships sebagai Strategi Pemasaran untuk Mencapai Keuntungan Jangka Panjang - Hannah Dara Vanzuela Garay (Jurnal Manajemen Maranatha, 2006)
With the realization of globalization in the world economies, market opportunities seem to be never-ending. Companies must be fast and always advance in achieving better performance and in delivering the optimal satisfaction for its customers. Internet has opened a superhighway of higher level of competition which information is vulnerable. Because of this by integrating the Internet technology into marketing strategy, companies will be able to enjoy the fullest competitive advantages offered by the internet. This article promotes web satisfaction and friendships as a means for company in achieving long term profitability. Consumers who are satisfied with the company’s website generate loyalty as seen the level of repurchase behavior, intention to buy and positive word of mouth. Meanwhile the degree of friendship also influences satisfaction between the interaction of provider and its customer.